Trading volume and liquidity provision in cryptocurrency markets - Daniele Bianchi; Mykola Babiak; Alexander Dickerson (Sveriges Riksbank, 2022)
We provide empirical evidence within the context of cryptocurrency markets that the returns from liquidity provision, proxied by the returns of a short-term reversal strategy, are primarily concentrated in trading pairs with lower levels of market activity. Empirically, we focus on a moderately large cross section of cryptocurrency pairs traded against the U.S. Dollar from March 1, 2017 to March 1, 2022 on multiple centralised exchanges. Our findings suggest that expected returns from liquidity provision are amplified in smaller, more volatile, and less liquid cryptocurrency pairs where fear of adverse selection might be higher. A panel regression analysis confirms that the interaction between lagged returns and trading volume contains significant predictive information for the dynamics of cryptocurrency returns. This is consistent with theories that highlight the role of inventory risk and adverse selection for liquidity provision.
Keywords: G12; G17; E44; C58; 330; Liquidity provision; short-term reversal; trading volume; empirical asset pricing; adverse selection